Pengaruh Metode Outdoor Learning Terhadap Keterampilan Menulis Teks Deskripsi Siswa - Milka Ria Daeli; Rosmawaty Harahap (LPPM Politeknik Pratama, 2023)
This study aims to determine the effect of the Outdoor Learning method on the skills of writing descriptive texts for class VII SMP Negeri 25 Medan in the 2022/2023 academic year. The method used in this thesis is an experimental method with a One group design. The population in this study were all students of class VII SMP Negeri 25 Medan. The sample in this study was class VII-G which consisted of 32 students. The data analysis technique used in this study is quantitative data by using analysis requirements test, homogeneity test and hypothesis testing. The results showed that the average score for writing descriptive text skills before applying the treatment was 63.75 belonging to the less category while the average value for writing descriptive text skills using the treatment was 82.21 belonging to the good category. Based on the t test, a significance level value of α = 0.05 is obtained with dk = N-1 = 31, so that a ttable value of 2.040 is obtained. Thus it is concluded that tcount > ttable, namely 8.961 > 2.040 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the Outdoor Learning learning method on the skills of writing descriptive texts for class VII students of SMP Negeri 25 Medan in the 2022/2023 Academic Year.